Academic Supervision and Adversity Quotient: Predictors of Pedagogical Competence Among Madrasah Tsanawiyah Teachers - Khairani Khairani; Sulastri Sulastri (Yayasan Darusssalam Bengkulu, 2026)
Pedagogical competence is one of the key determinants of instructional quality in Madrasah Tsanawiyah. This study aimed to examine the effects of academic supervision by madrasah principals and teachers' Adversity Quotient (AQ) on pedagogical competence, both individually and simultaneously. A quantitative research approach employing a correlational design was adopted. The study population comprised 818 Madrasah Tsanawiyah teachers in Rokan Hilir Regency, Indonesia, from which 124 respondents were selected using a multistage cluster stratified random sampling technique. Data were collected through Likert-scale questionnaires that had been validated and confirmed to be reliable. The data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression with the aid of IBM SPSS Statistics version 27. The findings revealed that academic supervision had a positive and statistically significant effect on teachers' pedagogical competence, explaining 76.8% of its variance (R² = 0.768). Similarly, Adversity Quotient exerted a positive and significant influence, accounting for 51.7% of the variance in pedagogical competence (R² = 0.517). Furthermore, academic supervision and Adversity Quotient jointly had a positive and statistically significant effect on teachers' pedagogical competence (R = 0.879, R² = 0.773, F = 206.234, p < .001), indicating that both variables collectively explained 77.3% of the variance in pedagogical competence. These findings underscore that strengthening academic supervision and enhancing teachers' resilience in coping with professional challenges through a higher Adversity Quotient are essential strategies for improving the pedagogical competence of Madrasah Tsanawiyah teachers.